ANALISIS KEPUTUSAN PEMILIHAN PENGUNJUNG PADA CAFE SEDULUR DIRGANTARA KECAMATAN PANTAI LABU DELI SERDANG SEBAGAI TEMPAT BEREKREASI - Syahrul, Syahrul (Akademi Pariwisata Darma Agung, 2025)
This study aims to analyze and understand the influence of service quality, ambiance, andfacilities on visitors' decisions to choose Cafe SedulurDirgantara in Kualanamu District, Deli Serdang Regency, North Sumatra. This research is a causal study that analyzes how one variable affects another. It isexploratoryin nature, conducted through direct field surveys. The sample for this study consisted of 200 selected individuals, chosen using an accidental sampling method. Data collection techniquesinvolved interviews and questionnaires using a 5-point Likert scale. Data analysis wasperformed using descriptive analysis with an impact analysis method. To test the hypotheses, acorrelation test was used to determine the overall interaction between variables. Subsequently, the data was analyzed using regression analysis with the aid of SPSS (Statistical Product and Service Solitions). The research results show that service quality has an influence on guest visit decisions of 0,212 and has a positive and significant relationship (tcount​ 5,398 >ttable​ 1.660) in the moderate category (r = 0.461, assessment criterion 0.40 - 0.599) on the decision to visit the cafe.Ambianceand facilities also have an influence on guest visit decisions of 0,287 with a positive andsignificant relationship (tcount​ 4,582 >ttable​ 1.660) in the moderate category (r = 0.403,assessment criterion 0.40 - 0.599) on the decision to visit Cafe SedulurDirgantaraKualanamu, Deli Serdang.